2021
DOI: 10.1192/j.eurpsy.2021.1044
|View full text |Cite
|
Sign up to set email alerts
|

Sexting in young university of the colombian caribbean, a comparative study between male and female

Abstract: IntroductionSexting is sending / forwarding erotic-sexual content voluntarily through technological devices and / or the internet. (Fleschler-Peskin, 2013). Real Participation (RPS), Active Disposition (ADS) and Emotional Expression (EES) was studied.ObjectivesCompare sexting in two groups of participants: female and maleMethodsComparison of data means measured by the Cronbach alpha sexting behavior scale α = 0.92, (Chacon-Lopez, et al, 2016). Sample N = 900 (447 female and 453 male)ResultsThe ADS and RPS decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Indeed, Colombian adolescents seem to report a higher number of sexual behaviors together with an earlier sexual debut, if compared to Spanish adolescents. Another recent study on Colombian Caribbean university students (Gonzalez et al, 2021 ) found that young adults decrease their engagement in sexting between 18 and 20 years old and increase it between 20 and 22. Moreover, young men were more likely to be involved in sexting than young women.…”
Section: Cross-cultural Differences In Sextingmentioning
confidence: 97%
“…Indeed, Colombian adolescents seem to report a higher number of sexual behaviors together with an earlier sexual debut, if compared to Spanish adolescents. Another recent study on Colombian Caribbean university students (Gonzalez et al, 2021 ) found that young adults decrease their engagement in sexting between 18 and 20 years old and increase it between 20 and 22. Moreover, young men were more likely to be involved in sexting than young women.…”
Section: Cross-cultural Differences In Sextingmentioning
confidence: 97%